Epidemiology and trends of animal bites in Khoy County, Northwest Iran: A retrospective study (2021–2024) - Parviz Shahmirzalou; Hassan Ebrahimpour Sadagheyani (PLoS ONE, 2026)
Background Animal bites are a significant global public health concern because they can lead to rabies, a disease with a very high case fatality. Therefore, this study aimed to describe the demographic and epidemiological characteristics of animal bite cases and to examine temporal trends in their incidence in Khoy County, Northwest Iran, from 21/03/2021–19/03/2024. Methods This registry-based, retrospective longitudinal study included all animal bite cases recorded in Khoy County between 21/03/2021 and 19/03/2024. Data on demographic characteristics, post-exposure preventive actions, and vaccination status were extracted. Analyses comprised descriptive statistics, chi-square tests in SPSS V17, trend analysis, time-series regression, and a 12-month forecast in Minitab V22. Results The mean age of bite victims was 31.23 years. The incidence of animal bites per 100,000 population in 2021–2024 was 371.39, 503.23, 506.02, and 397.45, respectively. Dogs accounted for 91% of bite incidents, and the most common circumstances leading to bites were sudden animal attacks, provoking the animal, hunting, and self-defense. Monthly counts revealed a clear 12-month seasonal variation, with the highest incidence occurring in summer and early autumn. The forecasting model predicted that late spring and summer of 2024 would be the peak periods for animal-bite incidence. Conclusion Due to the high rate of animal bites in Khoy County, it is advisable to focus on educating at-risk groups about prevention and encouraging prompt medical attention for post-exposure rabies prophylaxis when bites happen.